Convenient construction of fluorescent markers for lipid droplets with 1, 8-naphthalimide unit. (February 2021) - Ni, Jing-Yang; Weng, Xiao-Feng; Sun, Ru; Xu, Yu-Jie; Ge, Jian-Feng
Abstract: 1, 8-Naphthalimide is widely applied in the construction of probes because it is easy to be modified. However, 1, 8-naphthalimide has been reported rarely in the application of organelle labelling especially lipid droplets (LDs). Herein, three types of amine compounds, aliphatic amine (a, b ), aromatic amine (c, d ) and heterocyclic amine (e, f ), were chosen to construct fluorescent dyes (1a -1f ) with 4-bromo- N -butylnaphthalimide (1 ) by Ullmann reaction. The maximum emission wavelength ranged from 490 nm to 550 nm. What's more, 1a-1e showed high fluorescence quantum yields (0.54–0.93) in chloroform and 1e-1f had excellent photostability (>92%). In addition, the cell imaging experiment showed that they could label lipid droplets for HeLa cancer cells and L929 normal cells with extremely low toxicity. This work realizes the classical fluorophore 1, 8-naphthalimide to synthesize a series of LDs markers without complex synthesis steps. Graphical abstract: Image 1 Highlights: An easy way to synthesize a series of lipid droplets markers with 1, 8-naphthalimide unit. All the 1, 8-naphthalimide derivatives had high photostability and fluorescence quantum yield. All the markers showed extremely low toxicity to cells.